AIR QUALITY MONITORING WITH THE LICHEN BIODIVERSITY INDEX (LBI) IN THE DISTRICT OF FAENZA (ITALY) - Manuela Cioffi (EQA, 2009)
The Lichen Biodiversity Index (LBI) is a method for monitoring air pollution. This method employs lichens living on lime trees because they are sensitive to NOx and SOx, and it considers the variations in their communities. This study was performed in 16 stations located in the suburbs of Faenza city town and the result shows a more than acceptable air quality although in some stations the air was affected by the polluting effects of the vehicle traffic.